The CK1δ/ϵ-Tip60 Axis Enhances Wnt/β-Catenin Signaling via Regulating β-Catenin Acetylation in Colon Cancer - Ning, Jiong; Sun, Qi; Su, Zijie; Tan, Lifeng; Tang, Yun; Sayed, Sapna; Li, Huan; Xue, Vivian Weiwen; Liu, Shanshan; Chen, Xianxiong; Lu, Desheng (Frontiers in Oncology, 2022)
Casein kinase 1δ/ε (CK1δ/ε) are well-established positive modulators of the Wnt/β-catenin signaling pathway. However, the molecular mechanisms involved in the regulation of β-catenin transcriptional activity by CK1δ/ε remain unclear. In this study, we found that CK1δ/ε could enhance β-catenin-mediated transcription through regulating β-catenin acetylation. CK1δ/ε interacted with Tip60 and facilitated the recruitment of Tip60 to β-catenin complex, resulting in increasing β-catenin acetylation at K49. Importantly, Tip60 significantly enhanced the SuperTopFlash reporter activity induced by CK1δ/ε or/and β-catenin. Furthermore, a CK1δ/CK1ε/β-catenin/Tip60 complex was detected in colon cancer cells. Simultaneous knockdown of CK1δ and CK1ε significantly attenuated the interaction between β-catenin and Tip60. Notably, inhibition of CK1δ/ε or Tip60, with shRNA or small molecular inhibitors downregulated the level of β-catenin acetylation at K49 in colon cancer cells. Finally, combined treatment with CK1 inhibitor SR3029 and Tip60 inhibitor MG149 had more potent effect on downregulation of β-catenin acetylation and inhibition of cell growth. Taken together, our results revealed that the transcriptional activity of β-catenin could be modulated by the CK1δ/ε-β-catenin-Tip60 axis, which may be a potential therapeutic target for colon cancer.